LATTICE VALUED ALESHIN TYPE AUTOMATA WITH -MOVES - Jeyanthi, A.; Kalpana, V. (IJRDO -Journal of Computer Science Engineering, 2015)
The extended subset construction of lattice-valued Aleshin type finite automatais introduced, then the equivalences between lattice-valued finite automat , latticevalueddeterministic finite automata and lattice-valued finite automata with e-movesare proved. A simple characterization of lattice-valued languages recognized bylattice-valued finite automata is given, then it is proved that the Kleene theorem holdsin the frame of lattice-setting. A minimization algorithm of lattice-valueddeterministic finite automata is presented. In particular, the role of the distributive lawfor the truth valued domain of finite automata is analyzed: the distributive law is notnecessary to many constructions of lattice-valued finite automata, but it indeedprovides some convenience in simply processing lattice-valued finite automata